2011
DOI: 10.4103/0970-9290.80008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relative efficacy of autologous platelet-rich plasma in combination with β-tricalcium phosphate alloplast versus an alloplast alone in the treatment of human periodontal infrabony defects: A clinical and radiological study

Abstract: Combination of PRP and β-TCP led to a significantly more favorable clinical and radiographic improvement in infrabony periodontal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 0 publications
3
30
2
1
Order By: Relevance
“…However, comparison between the two groups revealed no statistically significant difference in the reduction of radiographic defect depth or the defect fill when measured at 6 and 9 months respectively. The results of this inter group comparison were found to be similar to the results of previously conducted studies by Camargo PM et al, (2009) [40] and Saini N et al, (2011) [35], where they found significant improvement in the test sites as compared to control sites in defect depth reduction and bone fill. Significant improvement in clinical and radiological parameters both at test and control sites may also be attributed to the physical characteristic of the regenerative materials used.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, comparison between the two groups revealed no statistically significant difference in the reduction of radiographic defect depth or the defect fill when measured at 6 and 9 months respectively. The results of this inter group comparison were found to be similar to the results of previously conducted studies by Camargo PM et al, (2009) [40] and Saini N et al, (2011) [35], where they found significant improvement in the test sites as compared to control sites in defect depth reduction and bone fill. Significant improvement in clinical and radiological parameters both at test and control sites may also be attributed to the physical characteristic of the regenerative materials used.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results on comparison between two groups were obtained in previous studies [23,24,[31][32][33][34], but contradictory results were found by Saini N et al, (2011), where there was significant reduction in PPD in test group compared to control group [35].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The platelet rich plasma + hydroxyapatite group showed a significantly greater probing depth reduction of (6.1± 3.6 mm) and relative attachment gain (7.1±4.1 mm) when compared to the saline hydroxyapatite who showed a probing depth reduction [15], Saini N et al 2011 [16], Kaushick BT et.al 2011 [17].Shreya Shetty et.al(2013) [18].Shakshi et.al have conducted a clinical study on platelet rich plasma and allograft and have concluded that platelet rich plasma enchances better regeneration with combined to allografts…”
Section: Discussionmentioning
confidence: 93%
“…Lukovic and associates conducted a clinical study that showed Cerasorb and Bioss have similar efficacies as a treatment for deep infrabony pockets (14). Saini and associates found limited improvement using beta tricalcium phosphate to treat infrabony defects and determined that beta tricalcium phosphate in combination with biologically active factors provides a significantly better result (15). Jansen and associates showed that the main shortcoming of beta tricalcium phosphate is its fast resorption and that priority in the treatment of bony defects should be given to autogenous transplants (16).…”
Section: Introductionmentioning
confidence: 99%